4w(w-3)=0

Simple and best practice solution for 4w(w-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w(w-3)=0 equation:


Simplifying
4w(w + -3) = 0

Reorder the terms:
4w(-3 + w) = 0
(-3 * 4w + w * 4w) = 0
(-12w + 4w2) = 0

Solving
-12w + 4w2 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '4w'.
4w(-3 + w) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0

Subproblem 2

Set the factor '(-3 + w)' equal to zero and attempt to solve: Simplifying -3 + w = 0 Solving -3 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + w = 0 + 3 Combine like terms: -3 + 3 = 0 0 + w = 0 + 3 w = 0 + 3 Combine like terms: 0 + 3 = 3 w = 3 Simplifying w = 3

Solution

w = {0, 3}

See similar equations:

| X+6=-2x-6 | | 2(2y-7)=3y+4 | | tan49=7/x | | (3y-20)(y+10)70=180 | | 10/87=x/100 | | s(n)=(1/4)n | | -7+2y=2y | | 8+2x-7-5x=3x+2-9x | | sin22=X/17 | | p*1=2 | | .4(d-2)=.3d+9-1+.1d | | -2x-4x=-3(-4x-6)+6(7-8x) | | v*8=16 | | -15k+9k=36 | | 4x+5/2x=1/2 | | 2z+16=58 | | 3d-4=d+11 | | 2(1.5y+2)=3y+4 | | 16=2x-4x | | -7c+10c=33 | | p+p+81=180 | | 3(t-4)-2(2t+3)=-4 | | 18=-9v | | 21-22= | | 3(x+12)=3x+12 | | 2p+81= | | Y+1.91=8.75 | | 4+6(n)=9(n)+10 | | -6=x-2-8 | | b+3.5=5.21 | | 6.25t=44.25 | | 4(-8x+-5)=-32x-26 |

Equations solver categories